Approaches to Promoting Inquiry Based Learning In the Classroom: A Comparative Study on the Impact of Inquiry-based Learning in Science Education (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In the sciences, inquiry-based learning has been widelypromoted to increase literacy and skill development, but there has been littlecomparison to more traditional curricula.In this study, we demonstrated greater improvements in students’ scienceliteracy and research skills using inquiry lab instruction. We also found thatinquiry students gained self-confidence in scientific abilities, buttraditional students’ gain was greater –likely indicating that the traditionalcurriculum promoted over-confidence. Inquiry lab students valued more authenticscience exposure but acknowledged that experiencing the complexity andfrustrations faced by practicing scientists was challenging, and may explainthe widespread reported student resistance to inquiry curricula.